Degree of the availability of the 21st century skills in the social studies textbooks of the twelfth grade of post-basic education in Sultanate of Oman - Alobeidani, Mohammed Juma Mohammed; Haron, Sueraya Che (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to determine the availability of 21st century skills are included in social studies books in the twelfth grade of post-basic education in the Sultanate of Oman. The study followed the analytical descriptive approach by following the content analysis method, and its sample consisted of social studies textbooks listed for the twelfth grade in the post-basic education stage for the academic year 2021/2022 AD which was selected from the study community, which includes all social studies books for basic education in its first and second cycles from the third to tenth grade, and post-basic education from the eleventh to the twelfth grade. In order to answer the questions of the study, the researcher prepared a card for content analysis that consisted of three main areas: the field of learning and creativity, the field of informational, media and technical culture, and the field of life and profession. From these areas emerged (11) main skills, (24) sub-skills, and (62) ) as an indicator of performance, and it was judged using the "Delphi" method in Two consecutive rounds, and this study resulted in many results, the most important of which are: There is a discrepancy in the distribution of twenty-first century skills in the study sample books, The most repetitions focus on the first area of ​​learning skills and creativity.The study recommended the necessity of including the skills of the twenty-first century in all social studies curricula and distributing them in a balanced manner.
Keywords: 21st Century Skills; Social Studies Books; 12th Grade; Post-Basic Education